Procedural provisions introduced by the Algerian legislator to combat cyber corruption crimes - Nadia, Zouggaghe (The International tax journal, 2026)
Information corruption crimes are considered among the most dangerous criminal phenomena threatening societies at various levels, given that they constitute one of the greatest obstacles to economic and social development. What has increased their seriousness is that many of their forms are no longer domestic crimes committed within the territory of a single State, but have crossed national borders as a result of globalization on the one hand, and the development of the mechanisms and means of committing them in parallel with the evolution of modern information and communication technologies on the other hand. In order to confront these evolving crimes, the Algerian legislator undertook to update its legal system by issuing new legal texts, mainly represented by Law No. 06-01 relating to the prevention of and fight against corruption, or by amending the legal texts in force, such as the Code of Criminal Procedure, so as to include special methods of prosecution and investigation that respond to the dynamic and organized nature of these crimes.